C-reactive protein, procalcitonin, interleukin-6, vascular endothelial growth factor and oxidative metabolites in diagnosis of infection and staging in patients with gastric cancer - Ilhan, Nevin; Ilhan, Necip; Ilhan, Yavuz; Akbulut, Handan; Kucuksu, Mehmet (Baishideng Publishing Group Inc, 2004)
AIM: The current study was to determine the serum/plasma levels of VEGF, IL-6, malondialdehyde (MDA), nitric oxide (NO), PCT and CRP in gastric carcinoma and correlation with the stages of the disease and accompanying infection. METHODS: We examined the levels of serum VEGF, IL-6, PCT, CRP and plasma MDA, NO in 42 preoperative gastric cancer patients and 23 healthy subjects. There were infection anamneses that had no definite origin in 19 cancer patients. RESULTS: The VEGF levels (mean +/- SD; pg/mL) were 478.05 +/- 178.29 and 473.85 +/- 131.24 in gastric cancer patients with and without infection, respectively, and these values were not significantly different (P>0.05). The levels of VEGF, CRP, PCT, IL-6, MDA and NO in cancer patients were significantly higher than those in healthy controls and the levels of CRP, PCT, IL-6, MDA and NO were statistically increased in infection group when compared with non-infection group (P<0.001). CONCLUSION: Although serum VEGF concentrations were increased in gastric cancer, this increase might not be related to infection. CRP, PCT, IL-6, MDA and NO have obvious drawbacks in the diagnosis of infections in cancer patients. These markers may not help to identify infections in the primary evaluation of cancer patients and hence to avoid unnecessary antibiotic treatments as well as hospitalization. According to the results of this study, IL-6, MDA, NO and especially VEGF can be used as useful parameters to diagnose and grade gastric cancer.
Keywords: Helicobacter-Pylori Infection; Acute-Phase Proteins; Nitric-Oxide; Tumor Angiogenesis; Permeability Factor; up-Regulation; Serum-Levels; Dna-Damage; Carcinoma; Expression